PENGARUH PEMASARAN INDUSTRI UMKM DI ERA DIGITAL TERHADAP TINGKAT PEMBELIAN KONSUMEN - SAMUEL TENANG UKUR ARDIANTA GINTING (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The use of technology for the benefit of marketing various products is a necessary reality. Included in this context is the use of digital media to market UMKM industrial products. This research aims to determine the effect of the use of digital media on the level of consumer purchases of MSME products in the city of Medan. The research method used in this study is descriptive quantitative. This research was conducted on a sample of 147 units with an error rate of 5%. The independent variable in this research is the use of digital media technology (X), and the dependent variable is the level of purchase (Y). The results prove that there is a positive and significant relationship between the use of digital media (X) and the level of consumer purchase (Y), which is a percentage of 69.2%. Thus, it can be said that the higher the use of digital media, the higher the level of purchases by consumers of these UMKM industrial products.